Generation anxiety : a Millennial and Gen Z guide to staying afloat in an uncertain world - Cook, Lauren (Abrams Image, 2023)
"Millennials and Gen Z-ers are considered two of the most anxious generations in history, and with the many intense generation-specific stressors they've had to face in recent years-including climate change, political polarization, systemic racism, gun violence, and financial instability-it's easy to see why people are being diagnosed with anxiety at alarming rates. Dr. Lauren Cook, a psychologist and career coach who specializes in treating Millennials and Gen Z patients-and a Millennial who also lives with anxiety-understands the many nuanced reasons why these two groups are struggling in different ways than their predecessors. Using a feminist and intersectional lens, Dr. Cook shares her own struggles with anxiety and provides easy, actionable steps to help readers ride the waves of anxiety rather than constantly swimming against them. This relatable, honest, and information-packed book incorporates thorough, evidence-backed psychological research and diverse client experiences to illustrate a broad range of presentations of anxiety to help readers gain insight into their own stressors and combat them"--